2013
DOI: 10.3168/jds.2012-5590
|View full text |Cite
|
Sign up to set email alerts
|

Development of probiotic dairy beverages: Rheological properties and application of mathematical models in sensory evaluation

Abstract: Strawberry-flavored probiotic dairy beverages (2% vol/vol Lactobacillus acidophilus) were produced using 0, 20, 35, 50, 65, and 80% (vol/vol) whey in their formulations. Mathematical models (survival analysis, minimal significant difference, and mean global acceptance) were used to identify the optimal (sensorially) whey concentration in probiotic beverages. Fifty-five consumers evaluated acceptance of the beverages using hybrid 9-point hedonic scales. In addition, Lb. acidophilus were enumerated and pH was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 45 publications
8
65
1
5
Order By: Relevance
“…Table 3 shows the values of pH for the fermented dairy beverages during refrigerated storage, varying from 3.69 (trial D) to 4.33 (trial G). Similar results were found by Tonguc et al (2013) in fermented milk and Castro et al (2013b) in probiotic dairy beverage. The pH values suffered several variations during the storage period.…”
Section: Statistical Analysis Of Datasupporting
confidence: 80%
“…Table 3 shows the values of pH for the fermented dairy beverages during refrigerated storage, varying from 3.69 (trial D) to 4.33 (trial G). Similar results were found by Tonguc et al (2013) in fermented milk and Castro et al (2013b) in probiotic dairy beverage. The pH values suffered several variations during the storage period.…”
Section: Statistical Analysis Of Datasupporting
confidence: 80%
“…The score for the peach beverage was 5.4 and that of the strawberry beverage was 6.2, based on a nine-point scale. Castro et al (2013) developed a probiotic whey-based beverage and found that beverages with whey contents greater than 65% resulted in lower sensory acceptance. They explained that greater amounts of whey results in a more astringency beverage, which is a negative factor.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Potwierdza to stwierdzenie Castro i wsp. [5], że zastąpienie mleka serwatką w napojach fermentowanych nie powoduje zmniejszenia przeżywalności bakterii probiotycznych.…”
Section: Przeżywalność Bakterii Probiotycznychunclassified